'We are just ordinary people working hard to reach our goals!' Disabled students' participation in Norwegian higher education. Issue 4 (21st April 2018) - Langørgen, Eli; Magnus, Eva
Abstract: In this article we shed light on the experiences of disabled students attending professional courses in higher education in Norway. The findings from this empirical study are based on interviews with 14 students with diverse impairments, ranging from the visible to the invisible. They faced barriers that they resolved to address on their own, using their capabilities and working 'in silence' to meet the expectations of normal students in academia as strong and independent. In addition to their own motivation and self-determination, what facilitated their progress in their studies was that some of the staff and fellow students met them respectfully as ordinary students, while recognizing their strain and providing support without calling attention to it. Leaning on the Nordic Relational Model of Disability, we call for greater awareness of the complex interactional processes between the disabled students and people in their social environment.